2017
DOI: 10.1515/ntrev-2017-0160
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanomaterials and their application to electrochemical sensors: a review

Abstract: Carbon has long been applied as an electrochemical sensing interface owing to its unique electrochemical properties. Moreover, recent advances in material design and synthesis, particularly nanomaterials, has produced robust electrochemical sensing systems that display superior analytical performance. Carbon nanotubes (CNTs) are one of the most extensively studied nanostructures because of their unique properties. In terms of electroanalysis, the ability of CNTs to augment the electrochemical reactivity of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
103
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(108 citation statements)
references
References 122 publications
0
103
0
Order By: Relevance
“…However, one should keep in mind that the critical length scale is not necessarily 100 nm, as it depends on the material and property under consideration . For carbon atoms, the main representative materials according to this classification are: buckyballs (linear or 0‐D), nanotubes (1‐D), graphene (plane or 2‐D), and diamond and graphite (tetrahedral or 3‐D), , see Figure .…”
Section: Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one should keep in mind that the critical length scale is not necessarily 100 nm, as it depends on the material and property under consideration . For carbon atoms, the main representative materials according to this classification are: buckyballs (linear or 0‐D), nanotubes (1‐D), graphene (plane or 2‐D), and diamond and graphite (tetrahedral or 3‐D), , see Figure .…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Carbon has long been applied as an electrochemical sensing interface owing to its versatility and unique electrochemical properties. Procedures in electroanalysis strongly depend on material aspects such as chemical and physical properties of electrode surfaces, the effects of the applied potential, adsorption, and coatings applied to the electrode surface to enhance detection , see Figure A. Carbon‐based nanostructures, such as carbon nanofibers, carbon nanotubes, and mesoporous carbons, have been extensively used in the fabrication of modified electrodes for applications in both, analytical and industrial electrochemistry.…”
Section: Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, the use of nanocomposite structures has been growing rapidly and has attracted much attention from scientific research communities [1,2]. Among the utilized nanofillers, CNT and graphene have become very popular due to their unique thermo-mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are very attractive in this area because they have a large surface area to volume ratio, permitting the surface to be used in an efficient way. It was reported that carbon nanomaterials can provide electrochemical biosensing for effective discovery of diseases such as cancers (Power, Gorey, Chandra, & Chapman, 2018).…”
Section: Introductionmentioning
confidence: 99%